STRATEGI GURU PENDIDIKAN ISLAM DALAM MENINGKATKAN KEMAHIRAN MEMBACA IQRA’ PESERTA DIDIK DI TADIKA TAHFIDZ NUR FURQAN, MALAYSIA - Reni Cahyati; Muhammad Qorib; Zuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the strategies employed by Islamic Education teachers to enhance students’ proficiency in reading Iqra’ at Tadika Tahfidz Nur Furqan, Malaysia. Learning to read Iqra’ serves as a crucial foundation for children to recognize Arabic letters before progressing to reading the Qur’an fluently. The study adopts a descriptive qualitative approach with data collected through observation, interviews, and documentation involving teachers and students. The findings reveal that teachers play a vital role in guiding, motivating, and cultivating students’ interest in Iqra’ learning. The strategies applied include individual and small-group approaches, demonstration of correct pronunciation, repetitive reading exercises, and motivational reinforcement through praise and rewards. Teachers also utilize visual and audio media such as flashcards and hijaiyah songs to make learning more engaging and interactive. Beyond improving technical reading skills, Iqra’ instruction also contributes to the spiritual and moral development of students by instilling values such as discipline, respect, and love for the Qur’an. The study emphasizes that the success of Iqra’ learning depends not only on the teaching method but also on the teacher’s creativity, sincerity, and exemplary conduct in the learning process. Through effective strategies and engaging learning environments, Islamic Education teachers can foster active and meaningful learning experiences, shaping a generation of young Muslims who are not only skilled in reading the Qur’an but also embody Islamic character, noble morals, and a lifelong passion for Qur’anic literacy from an early age.